Tripodal amphiphiles tunable for self-assembly to polymersomes - Jun, Yong Joo; Park, Min Kyoung; Jadhav, Vithal B.; Song, Ju Hee; Chae, Song Wha; Lee, Hwa Jeong; Park, Kyung Su; Jeong, Byeongmoon; Choy, Jin Ho; Sohn, Youn Soo (ELSEVIER, 2010)
Cyclotriphosphazenes grafted with equimolar amounts of a hydrophilic polyethylene glycol and a hydrophobic oligopeptide in cis-nongeminal way form a new class of tripodal amphiphiles allowing both intra- and intermolecular hydrophobic interactions that differ from linear block copolymer amphiphiles. It has been found in this study that the tripodal amphiphiles can be tuned for self-assembly from micelles to bilayered polymersomes by controlling the hydrophobicity of the oligopeptide grafted. For instance, the tripodal amphiphiles with an intermediate hydrophobicity (O < log P < 1) (P = [solute](n-octanol)/[solute](water)) reassemble from initially formed micelles into polymersomes, whereas the trimers bearing highly hydrophobic oligopeptides (log P > 1) remain as stable micelles in aqueous solution. These biodegradable polymersomes exhibit outstanding physicochemical properties required for practical drug delivery and other biomedical applications. In particular, the cyclic phosphazene trimer platinated with a hydrophobic cis-bis (cyclohexylamine)Pt-moiety forms very stable polymersomes with excellent tumor selectivity by EPR effect and seems to be a promising candidate for preclinical studies. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: MACROMOLECULAR THERAPEUTICS; DRUG-DELIVERY; MICELLES